KONTRIBUSI SISTEM AMONG TERHADAP INKLUSI SOSIAL: STUDI KASUS DI SD TAMANSISWA YOGYAKARTA - Miftakhuddin Miftakhuddin; Muhammad Khoiron; Neni Wahyuningtyas (Jurnal Praksis dan Dedikasi Sosial (JPDS), 2023)
THE AMONG SYSTEM'S CONTRIBUTION TO SOCIAL INCLUSION: CASE STUDY AT TAMANSISWA YOGYAKARTA ELEMENTARY SCHOOLTamansiswa’s among system is a unique teaching model. The teaching model belongs to the family of non-directive. In practice, the among system is founded on Tamansiswa's philosophy and belief about the development of students’ knowledge and character, allowing them to be free to explore their surroundings. So far, the among system has helped to establish both theoretical and practical frameworks for social inclusion. However, the among system has received little attention because it is only used in private schools, which the community considers to be less legitimate. This study aims to investigate the why and how among system contributes to social inclusion. In-depth interviews, participatory observation, recording, and anecdotal notes were used to collect data, which was subsequently validated via triangulation. Data were then analyzed following the procedure introduced by Miles. Based on this analysis, the following important findings are highlighted: (a) the among system promotes Gender Equality and Social Inclusion (GESI), (b) the among system prioritizes the fulfillment of children’s rights to receive adequate education and development services over academic knowledge, and (c) the among system employs the humanism-constructivism paradigm (avoiding behaviorism). Practically, this foundation is manifested by the teacher by making friends with students based on the norms of politeness, respecting the child’s natural traits, and supervising the child in exercising his or her freedom (both freedom of thought, speech, and action). The findings of this study have significance for the necessity for the adoption of the among system in social studies course in order to develop social studies learning that is based on genuine experiences in a social environment (contextual). This study's findings also contribute to the development of core concepts for implementing the Fun School Movement, culture-based schools, and schools for children with special needs.Sistem among merupakan suatu model pengajaran yang khas perguruan Tamansiswa. Model pengajaran tersebut termasuk dalam rumpun model pengajaran non direktif. Dalam praktiknya, sistem among didasarkan kepada falsafah dan keyakinan Tamansiswa tentang perkembangan pengetahuan dan budi pekerti pelajar, agar mereka merdeka dalam mengenal dunianya. Selama ini, sistem among menyumbang kerangka teoretik maupun praktik terhadap pembangunan inklusi sosial. Namun sampai saat ini sistem among kurang diteliti karena hanya terselenggara di sekolah swasta yang oleh masyarakat dianggap kurang bonafit. Riset ini berusaha menelaah mengapa dan bagaimana kontribusi sistem among terhadap inklusi sosial secara detail dan mendalam. Data diperoleh melalui wawancara mendalam, observasi partisipatif, dokumentasi, dan catatan anekdot, kemudian divalidasi melalui triangulasi. Data yang sahih dianalisis mengikuti prosedur yang diperkenalkan Miles. Berdasarkan analisis tersebut, riset ini menyoroti temuan penting berikut: (a) sistem among mempromosikan Gender Equality and Social Inclusion (GESI), (b) alih-alih memprioritaskan pengetahuan akademik, sistem among memprioritaskan pemenuhan hak anak untuk mendapat layanan pendidikan yang layak dan pengembangan budi pekerti, dan (c) sistem among menggunakan paradigma humanisme-konstruktivisme (menghindari pola-pola behavioristik). Secara praktis, landasan tersebut dimanifestasikan guru dengan menjalin pertemanan dengan siswa berdasarkan norma kesopanan, menghormati kodrat alamiah anak, dan mengawasi anak dalam menggunakan kebebasannya (baik kebebasan berpikir, berucap, maupun bertindak). Temuan riset ini berimplikasi kepada perlunya adopsi sistem among dalam pembelajaran IPS agar tercipta pembelajaran IPS berbasis pengalaman riil di lingkungan sosial (kontekstual). Temuan riset ini juga berkontribusi kepada penambahan dasar-dasar pelaksanaan Gerakan Sekolah Menyenangkan (GSM), sekolah berbasis kebudayaan, dan sekolah yang mendidik anak berkebutuhan khusus.